Genome editing for improving nutritional quality, post-harvest shelf life and stress tolerance of fruits, vegetables, and ornamentals - Sharma, Punam; Pandey, Anuradha; Malviya, Rinku; Dey, Sharmistha; Karmakar, Subhasis; Gayen, Dipak (Frontiers in Genome Editing, 2023)
Agricultural production relies on horticultural crops, including vegetables, fruits, and ornamental plants, which sustain human life. With an alarming increase in human population and the consequential need for more food, it has become necessary for increased production to maintain food security. Conventional breeding has subsidized the development of improved verities but to enhance crop production, new breeding techniques need to be acquired. CRISPR-Cas9 system is a unique and powerful genome manipulation tool that can change the DNA in a precise way. Based on the bacterial adaptive immune system, this technique uses an endonuclease that creates double-stranded breaks (DSBs) at the target loci under the guidance of a single guide RNA. These DSBs can be repaired by a cellular repair mechanism that installs small insertion and deletion (indels) at the cut sites. When equated to alternate editing tools like ZFN, TALENs, and meganucleases, CRISPR- The cas-based editing tool has quickly gained fast-forward for its simplicity, ease to use, and low off-target effect. In numerous horticultural and industrial crops, the CRISPR technology has been successfully used to enhance stress tolerance, self-life, nutritional improvements, flavor, and metabolites. The CRISPR-based tool is the most appropriate one with the prospective goal of generating non-transgenic yields and avoiding the regulatory hurdles to release the modified crops into the market. Although several challenges for editing horticultural, industrial, and ornamental crops remain, this new novel nuclease, with its crop-specific application, makes it a dynamic tool for crop improvement.